Persuasive Strategien auf den Internetseiten für Verhütungsmittel - Maciejewski, Marcin (Studia Germanica Posnaniensia, 2019)
The article discusses typical persuasive strategies used by leading producers of contraceptives on their websites and on the websites of particular contraceptive products from the media-linguistic point of view. The purpose of the paper is to examine illocutions, text-clusters and the text-image relation through which the author wants to persuade about the quality of his products and to present arguments for using hormonal contraception. The article also shows which strategies are used to advertise the pill as a lifestyle and beauty product.